Labour intermediation as a mechanism for the labour market inclusion of persons with disabilities. Effectiveness and contribution to decent work - González Santana, Judith (LABOS Revista de Derecho del Trabajo y Protección Social, 2026)
The article analyses the labour intermediation system in relation to persons with disabilities within the framework of Employment Law 3/2023, starting from the persistent difficulties in accessing the labour market and in the quality of employment. It examines the legal configuration of the labour intermediation model as an instrument for labour inclusion and for the promotion of equal treatment and equal opportunities. The study shows that, despite the regulatory redefinition of the system, its practical effectiveness in the labour inclusion of this group remains limited. It concludes that these limitations reduce its capacity to contribute effectively to equality of opportunity in access to employment and to progress towards working conditions consistent with the concept of decent work promoted by the International Labour Organization.